Premenstrual Syndrome and Subsequent Risk of Hypertension in a Prospective Study - Bertone-Johnson, Elizabeth R. (Am J Epidemiol, 2015)
The prevalence of hypertension is increasing among younger women, and new strategies are needed to identify high-risk women who should be targets for early intervention. Several mechanisms underlying hypertension might also contribute to premenstrual syndrome (PMS), but whether women with PMS have a higher risk of subsequently developing hypertension has not been assessed. We prospectively evaluated this possibility in a substudy of the Nurses' Health Study II. Participants were 1,257 women with clinically significant PMS (1991–2005) and 2,463 age-matched comparison women with few menstrual symptoms. Participants were followed for incident hypertension until 2011. Over 6–20 years, hypertension was reported by 342 women with PMS and 541 women without. After adjustment for age, smoking, body mass index, and other risk factors for hypertension, women with PMS had a hazard ratio for hypertension of 1.4 (95% confidence interval: 1.2, 1.6) compared with women without PMS. Risk was highest for hypertension that occurred before 40 years of age (hazard ratio = 3.3; 95% confidence interval: 1.7, 6.5; P for interaction = 0.0002). The risk associated with PMS was not modified by use of oral contraceptives or antidepressants but was attenuated among women with high intakes of thiamine and riboflavin (P < 0.05). These results suggest that PMS might be associated with future development of hypertension and that this risk may be modifiable.